2016
DOI: 10.1007/s10126-016-9687-7
|View full text |Cite
|
Sign up to set email alerts
|

Editing of the Luteinizing Hormone Gene to Sterilize Channel Catfish, Ictalurus punctatus, Using a Modified Zinc Finger Nuclease Technology with Electroporation

Abstract: Channel catfish (Ictalurus punctatus) is the most important freshwater aquaculture species in the USA. Genetically enhanced fish that are sterile could both profit the catfish industry and reduce potential environmental and ecological risks. As the first step to generate sterile channel catfish, three sets of zinc finger nuclease (ZFN) plasmids targeting the luteinizing hormone (LH) gene were designed and electroporated into one-cell embryos, different concentrations were introduced, and the Cel-I assay was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(33 citation statements)
references
References 53 publications
0
32
0
1
Order By: Relevance
“…Reverse genetics research on animals and plants was largely pushed ahead by zinc finger nucleases (ZFNs), transcription activator-like effector nucleases (TALENs) and clustered regularly interspaced short palindromic repeats (CRISPR) ( Gaj et al, 2013 ), which showed great potential to modify genes of interest ( Ding et al, 2013 ). Until now, targeted gene editing has been reported in zebrafish, medaka, Nile tilapia, rainbow trout, common carp, channel catfish, rohu ( Labeo rohita ), Chinese tongue sole ( Cynoglossus semilaevis ), rice field eel ( Monopterus albus ), and so on ( Doyon et al, 2008 ; Ansai et al, 2014 ; Li et al, 2014 ; Yano et al, 2014 ; Chakrapani et al, 2016 ; Qin et al, 2016 ; Zhong et al, 2016 ; Cui et al, 2017 ; Feng et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Reverse genetics research on animals and plants was largely pushed ahead by zinc finger nucleases (ZFNs), transcription activator-like effector nucleases (TALENs) and clustered regularly interspaced short palindromic repeats (CRISPR) ( Gaj et al, 2013 ), which showed great potential to modify genes of interest ( Ding et al, 2013 ). Until now, targeted gene editing has been reported in zebrafish, medaka, Nile tilapia, rainbow trout, common carp, channel catfish, rohu ( Labeo rohita ), Chinese tongue sole ( Cynoglossus semilaevis ), rice field eel ( Monopterus albus ), and so on ( Doyon et al, 2008 ; Ansai et al, 2014 ; Li et al, 2014 ; Yano et al, 2014 ; Chakrapani et al, 2016 ; Qin et al, 2016 ; Zhong et al, 2016 ; Cui et al, 2017 ; Feng et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…自此, 基因组编辑在多种养殖鱼类中得到了应用, 如虹 鳟 [151] 、罗非鱼 [152] 、鲤 [153] 、大西洋鲑 [154] 、斑点叉尾 鮰 [155] 、黄鳝 [156] 、半滑舌鳎 [157] 和小体鲟 [158] 等. 基因 组编辑技术将在水产养殖动物基因功能解析和经济性 状精准设计育种中发挥重要作用 [102,145,149] .…”
Section: 基于全基因组信息及分子设计等前沿育种 技术unclassified
“…Zinc fingers have gene-targeting frequencies of up to 20% success (Porteus & Carroll 2005). In channel catfish, the overall mutation rate for three ZFN sets was 19.7%, with one ZFN set inducing average mutation rate of 38.5% in two of the treatments (Qin et al 2016). Because of greater costs, complexity of design, off-target effects, cytotoxicity and lower mutation rate, research on ZFNs is decreasing, especially once TALENs became available.…”
Section: Zfnsmentioning
confidence: 99%